A weberian analysis of the gestation of domination structures in trade unions - Santos-Silva, Antônio; Carvalho Neto, Antonio Moreira de (Revista de Administração da UFSM, 2020)
This paper presents the report of a survey that aimed to investigate the role of union leaders in gestation structures of domination in Brazilian unions adopting an interpretative Weberian analysis. Weberian concepts, such as domination, social relation and legitimacy were articulated to explain, in a qualitative approach, the internal social relations within trade unions. The exploratory analysis of 26 interviews conceded by trade union leaders allowed the identification of five groups of orders that constitute maxims and rules of action among the union leaders. This paper focuses on the documental analysis of 115 documents looking for evidence of the domination structures genesis. The documents revealed that these structures go back to the trade union training process, especially from the decade 1970s. The data analysis was structured in five groups of orders: ethics; political repression; ideology; mistrust between parts; and validity of laws. The study concluded by the pertinence of the adoption of the interpretative Weberian approach to explain the action of administrative staff (as in Weber, the influential individuals on the decision making process within the organization) related to the making and preservation of the structures of domination, confirming the Weberian theory.